2009
DOI: 10.1021/bc800547c
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Functionalized Nanogels for Targeted siRNA Delivery

Abstract: A major bottleneck in the development of siRNA therapies is their delivery to the desired cell type or tissue, followed by effective passage across the cell membrane with subsequent silencing of the targeted mRNA. To address this problem, we describe the synthesis of core/shell hydrogel nanoparticles (nanogels) with surface-localized peptides that specifically target ovarian carcinoma cell lines possessing high expression levels of the Eph2A receptor. These nanogels are also demonstrated to be highly effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
196
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(197 citation statements)
references
References 55 publications
1
196
0
Order By: Relevance
“…Blackburn et al prepared a peptide-functionalized core/shell nanogel for cancer cell specific siRNA delivery (Blackburn et al, 2009). This core/shell nanogel was composed of cross-linked poly(N-isopropylmethacrylamide) (pNIPMAm), an amphiphilic, thermoresponsive polymer that was strongly hydrated at physiological temperature.…”
Section: Nanogelmentioning
confidence: 99%
“…Blackburn et al prepared a peptide-functionalized core/shell nanogel for cancer cell specific siRNA delivery (Blackburn et al, 2009). This core/shell nanogel was composed of cross-linked poly(N-isopropylmethacrylamide) (pNIPMAm), an amphiphilic, thermoresponsive polymer that was strongly hydrated at physiological temperature.…”
Section: Nanogelmentioning
confidence: 99%
“…In this context, fluorescent co-monomers can be copolymerized into the polymer network, allowing for confocal fluorescence microscopy imaging [33]. Fluorescent energy transfer studies have been performed during the collapse of pNIPAM-based core-shell systems containing donor and acceptor fluorophores, respectively [34].…”
Section: Pnipam Microgels and Nanoparticlesmentioning
confidence: 99%
“…An example comprises core-shell pNIPAMbased beads with sizes below 100 nm (nano-gels), loaded with small interfering RNA (SiRNA). It has been shown that these systems bioconjugated with peptides can carry out selective targeting and SiRNA delivery to ovarian cancer cells, thereby reducing gene expression [33]. The ability of analytes to diffuse through the micro-or nanogel layer allows for a vast palette of potential detection routes as described below.…”
Section: Applications Of Pnipam Microgelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanogels, which have been widely used in drug delivery and medical diagnosis, can also deliver siRNA to targeted cells [93]. Nanogels are able to be loaded with siRNA via "breathing-in" manner besides electrostatic attraction [94]. Dickerson et al [95] investigated core/shell nanogels composed of poly (N-isopropylmethacrylamide) (pNIPMAm) cross-linked with N,N′-methylene(bisacrylamide) to deliver siRNA targeting epidermal growth factor receptor (EGFR).…”
Section: Other Nanocarriersmentioning
confidence: 99%